2013
DOI: 10.1371/journal.pone.0069650
|View full text |Cite
|
Sign up to set email alerts
|

How Long and Low Can You Go? Effect of Conformation on the Risk of Thoracolumbar Intervertebral Disc Extrusion in Domestic Dogs

Abstract: Intervertebral disc extrusion (IVDE) is a common neurological disorder in certain dog breeds, resulting in spinal cord compression and injury that can cause pain and neurological deficits. Most disc extrusions are reported in chondrodystrophic breeds (e.g. Dachshunds, Basset Hounds, Pekingese), where selection for ‘long and low’ morphologies is linked with intervertebral discs abnormalities that predispose dogs to IVDE. The aim of this study was to quantify the relationship between relative thoracolumbar verte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
75
1
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(86 citation statements)
references
References 45 publications
0
75
1
10
Order By: Relevance
“…[1][2][3][4]6,12,13,22,27,28 It has been demonstrated that English Cocker Spaniels have a less pronounced chondrodystrophic phenotype than Dachshunds. 5 The vertebral column length relative to the height at the withers (most dorsal aspect of the shoulders between the scapulae) was much higher in Dachshunds than in English Cocker Spaniels, but was similar between English Cocker Spaniels and German Shepherd Dogs. 5 It is therefore possible that different etiologic factors contribute to varying degrees in the development of IVDE in English Cocker Spaniels and Dachshunds.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…[1][2][3][4]6,12,13,22,27,28 It has been demonstrated that English Cocker Spaniels have a less pronounced chondrodystrophic phenotype than Dachshunds. 5 The vertebral column length relative to the height at the withers (most dorsal aspect of the shoulders between the scapulae) was much higher in Dachshunds than in English Cocker Spaniels, but was similar between English Cocker Spaniels and German Shepherd Dogs. 5 It is therefore possible that different etiologic factors contribute to varying degrees in the development of IVDE in English Cocker Spaniels and Dachshunds.…”
Section: Discussionmentioning
confidence: 91%
“…[23][24][25] Chondrodystrophy is characterized by disturbed endochondral ossification, so that affected dogs have disproportionally short limbs and relatively long spines. 5,22,26 This was highlighted in a recent study, 5 in which investigators found that dogs with shorter limbs and longer backs were at increased risk of developing thoracolumbar IVDE than were dogs with longer limbs and shorter backs. However, strict criteria to define a breed as chondrodystrophic are lacking, 1,9,27 and it is currently unclear whether English Cocker Spaniels should be considered chondrodystrophic.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Intervertebral disc extrusion (IVDE) is the most common cause of acute spinal cord injury (SCI) in dogs, and chondrodystrophic breeds such as the Dachshund, Cocker spaniel, Basset hound, Beagle, Pekingese, Shih Tzu, Miniature poodle and Bichon frise are commonly represented in the literature (Olby et al, 2003; Ito et al, 2005; Levine et al, 2011; Aikawa et al, 2012; Bergknut et al, 2012; Packer et al, 2013). The high incidence of spontaneous SCI in dogs makes them an important animal model for human SCI (Rice et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Despite decades of research to identify the new therapeutics, there has been only limited progress toward the beneficial findings. Thoracolumbar intervertebral disk herniation is the most common naturally occurring spinal disease in dogs and results in compressive and contusive SCI [2,7,10]. The most common treatment for SCI is early stabilization of the spinal column followed by surgical decompression and stabilization and minimizing secondary changes [6].…”
mentioning
confidence: 99%